Management of material and production problems arising from the technological and price developments in semiconductor devices : a study of Finnish electronics manufacturers - Ikegwuonu, Godwin (Report / Helsinki University of Technology. Industrial Economics and Industrial Psychology, 1988)
Selected sections in Finnish.